Ferroptosis in osteoarthritis: metabolic reprogramming, immunometabolic crosstalk, and targeted intervention strategies - Xia, Shenglin; Li, Li; Shi, Zhexiong; Sun, Nianyi; He, Yu (Frontiers in Immunology, 2025)
Osteoarthritis is a common degenerative joint disease characterized by progressive cartilage loss, bone remodeling, and chronic joint inflammation, yet its underlying mechanisms remain incompletely understood. Disrupted iron metabolism, particularly iron accumulation in joint tissues, contributes to oxidative damage and inflammation, suggesting a potential link to disease progression. This review focuses on ferroptosis, a regulated form of cell death driven by iron-dependent lipid peroxidation, as a key pathological mechanism in osteoarthritis. We summarize current evidence showing how impaired iron homeostasis, weakened antioxidant defenses, and metabolic alterations make chondrocytes and other joint cells vulnerable to ferroptotic injury. We further describe how inflammatory and metabolic signals interact to amplify ferroptosis, creating a self-reinforcing cycle of tissue damage. Finally, we explore emerging strategies to target ferroptosis, including iron chelation, antioxidant therapy, inhibition of lipid peroxidation, and gene or cell-based interventions. By integrating these findings, this review offers new insights into the role of ferroptosis in joint degeneration and highlights its potential as a therapeutic target in osteoarthritis.